2016
DOI: 10.1590/1809-4392201502502
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and capacity to promote maize growth of bacteria isolated from the Amazon region

Abstract: Maize plants can establish beneficial associations with plant growth-promoting bacteria. However, few studies have been conducted on the characterization and inoculation of these bacteria in the Amazon region. This study aimed to characterize endophytic bacteria isolated from maize in the Amazon region and to assess their capacity to promote plant growth. Fifty-five bacterial isolates were obtained from maize grown in two types of ecosystems, i.e., a cerrado (savanna) and a forest area. The isolates were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Maize was selected as a model organism because it also belongs to the Poaceae family, grows fast (Wang et al 2016), and because the same bacterial species have been described in both plants (Taulé et al 2012, Silva et al 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize was selected as a model organism because it also belongs to the Poaceae family, grows fast (Wang et al 2016), and because the same bacterial species have been described in both plants (Taulé et al 2012, Silva et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…This is the case of members of the Enterobacteriaceae family, which have been described as plant growth promoters in sugarcane and maize (Taulé et al 2012, Silva et al 2016). …”
Section: Abstract Resumomentioning
confidence: 99%
“…A produção dessa auxina é uma característica comum em bactérias endofíticas e tem sido observada em diversas espécies vegetais tais como milho (SILVA et al, 2016), batata (OGATA-GUTIÉRREZ et al, 2016) e diversas plantas medicinais (KHAN et al, 2017). Embora os endofíticos sejam capazes de produzir um grande número de fitohormônios, as auxinas e, em especial, o ácido-3-indol ácetico (AIA) são os mais comumente gerados.…”
Section: Resultsunclassified
“…A maior aplicação pauta-se na promoção do crescimento vegetal, sobretudo na capacidade de solubilizar fosfato inorgânico, fixar nitrogênio na forma de amônio, induzir resistência a patógenos por meio da produção de sideróforos e fitohormônios (PEREIRA et al, 2016).…”
Section: Introductionunclassified
“…and 99 to 137 %, respectively (Table 3). Silva et al (2016) reported the capacity of Pantoea and Bacillus to increase shoot and root dry matter by 28 % and 18 %, respectively, in maize plants at 40 days after emergence compared to un-inoculated control. Qureshi et al (2013) showed that the genus Rhizobium is an effective plant growth promoter in maize cultivars, due to its ability to improve the photosynthetic rate, up to 21 %.…”
Section: Maize Growth Promotion By Isolated Bacterial Strains Under G...mentioning
confidence: 99%